2021
DOI: 10.1111/jne.13029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pubertal onset on region‐specific Esr2 expression

Abstract: In female rats, pubertal onset is associated with maturation of the medial prefrontal cortex (mPFC) and mPFC-mediated behaviours. These behavioural and anatomical changes are likely a result of the effects of oestrogens at the nuclear oestrogen receptor (ER)β, which is expressed at higher levels than the ERα isoform in the adult How to cite this article: Drzewiecki CM, Sellinger EP,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 62 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…The pre‐ and post‐pubertal females were littermates at the same age. * p < .05, ** p < .01 (Drzewiecki et al., 2021).…”
Section: The Role Of Pubertymentioning
confidence: 99%
See 3 more Smart Citations
“…The pre‐ and post‐pubertal females were littermates at the same age. * p < .05, ** p < .01 (Drzewiecki et al., 2021).…”
Section: The Role Of Pubertymentioning
confidence: 99%
“…This occurred in parallel in both sexes in spite of a main effect of sex such that females had lower PPI scores than males. It is also notable that the age of the post‐pubertal females overlapped the age of the peripubertal males (Drzewiecki, Willing et al., 2021).…”
Section: Timing Within Adolescence Mattersmentioning
confidence: 99%
See 2 more Smart Citations
“…Although using in situ hybridization, a few groups ( 15 , 16 ) detected no expression of ERα and ERβ mRNA in the striatum, the majority of previous studies showed that the expression of estrogen receptors in the rodent dorsal striatum was sparse and was weak to moderate even in positive cells ( 17 22 ). In addition, recent findings demonstrate that ERα and ERβ expression are high in mouse pups and decreases with time resulting in low or very low expression in adults ( 23 , 24 ). Finally, ERα and GPER1 were detected in a small proportion of cholinergic interneurons using electron microscopy ( 17 ).…”
Section: Introductionmentioning
confidence: 99%